Overexpression of HER2 protein in lymph node-negative breast cancer patients - Kłosowska, Anna; Skręt, Joanna; Chmaj-Wierzchowska, Karolina (Contemporary Oncology/Współczesna Onkologia, 2002)
Aim: The aim of this study was to analyse the expression of the human epidermal growth factor receptor - 2 (HER2) in patients with no detected lymph node metastases, tumor size below 5 cm and in G2 stage. HER2 is a product of an HER2 proto-oncogen. It plays an important role in regulating cell growth. HER2 overexpression is generally associated with a more aggressive disease and a worse prognosis.The cases were those of patients treated by the Surgical Ward of Oncology Department of Karol Marcinkowski University of Medical Sciences in years 1999 and 2000. Materials and methods: We identified 36 cases suitable for inclusion in the study. Variables taken into consideration included the age of patients, histological type, size of tumor, grading, status of lymph nodes, the presence of estrogen and progesterone receptors, p53 and catepsin D in breast cancer cells. The patients were aged between 36 and 82 years. 72.2% of cases were ductal breast cancer. 72.2% of tumors had below 2 cm in diameter. Estrogen receptors were found in 75% of cases and progesterone receptors in 80.6%. Expression of 53 was detected in 52.8% of women. Expression of HER2 was detected using the \"DAKO HercepTest for Immunoenzymatic Staining (DAKO-Code No. 5204)\". Results and Conclusions: Overexpression of HER2 protein was detected in 11 patients (36%). Premenopausal women showed higher expression of HER2 (42.9%). Only two cases of lobular cancer did not provide adequate data for estimation of a relationship between histological type and expression of HER2. The size of the tumor did not appear to influence HER2 expression. Overexpressionof HER2 was detected in 33,3% of cases which were also tested positive for estrogen receptors. The presence of HER2 in these cases is indicative of a more aggressive form of disease which, in turn, is suggestive of resistance to hormonal therapy normally used in cases where estrogen receptors are detected. Presence or absence of p53 protein does not appear to have any bearing on HER2 expression. Conclusion: Overexpression of protein HER2 was detected in 30.6% patients, which allows the selection of those patients with a worse prognosis.